Confucianism in the China Model: Redefining China’s Modernization Through the Perspective of Cultural Relativism - Li, Cheukho (2023)
Despite the cultural difference, Latin America and China share similar historical trajectory of colonization and semi-colonization. This paper adopts the perspectives of cultural relativism and multiple modernities to examine how various actors in both regions have embarked on promoting Indigenous social, cultural and political movements in order to refine national identity and modernity, which deviates from hegemonic Western ideologies. This paper discuss Latin America’s Indigenous people and nations asserting their rights to protect their traditional homelands, culture, and self-determinations. The authors then argue that a similar pattern exists in the debate China Model’s distinctiveness and scrutinize how ethnic Chinese scholars may construct the China Model as its own form of “Indigenous” self-determination, cultural relativity, and equality. This paper examine how the discourses of China Models’ proponents are in-line with asserting Chinese modernity that mirrors Latin American Indigenous movements to be recognised as sovereign and equal nations.